Solitary Tibial Osteolytic Lesion - Emilios E. Pakos; Dimitrios N. Gartzonikas; Pericles G. Tsekeris; Theodore A. Xenakis (Case Reports in Medicine)
We report an unusual case of solitary osteolytic tibial metastasis from a primary endometrial cancer in a 62-year-old woman. The primary cancer was treated with total abdominal hysterectomy and bilateral salpingo-oophorectomy combined with postoperative external beam radiotherapy, while the tibial metastasis was treated with an above knee amputation. The rarity of the case lies on the fact that metastases distally to the elbow and knee are uncommon and endometrial cancer rarely gives distal bone metastases and particularly solitary to the extremities.